Development of a Snack Box Flip Book for Culinary Business Management Course - Titis Budi Rahayu; Mulyadi, Mentari Arisyid; Azmi, Chairiza (Universitas Negeri Semarang, 2025)
The use of instructional media in the Culinary Business Management course within the Culinary Education Program at Unimed remains limited to PowerPoint presentations and general business management textbooks. Students are struggling to effectively determine Snack Box menus and design practical activities. Therefore, students need a practical learning medium that can support in planning their practical work. The objectives of this study are: (1) To produce a Flip Book-based learning media on Snack Box material; (2) To analyze the feasibility of the Snack Box Flip Book according to material experts and media experts; (3) To analyze student satisfaction with the Snack Box Flip Book. The research method used is Research and Development (R&D) with a 4-D approach. Data collection techniques include needs analysis observation, feasibility test questionnaires, and student satisfaction questionnaires regarding the Snack Box Flip Book. The conclusions are: (1) The development of the Snack Box Flip Book was carried out using the 4-D model, consisting of the following stages: (a) Define, (b) Design, (c) Develop, (d) Disseminate; (2) The feasibility test results from material and media experts obtained a score of 3.32, categorized as feasible; and (3) The student satisfaction assessment resulted in a score of 3.44, categorized as very satisfied. The use of the Snack Box Flip Book offers the benefit of enabling students are creatively and independently determine Snack Box menus and implement them in practice with results that meet established standards.